Effectiveness of Low-Level Laser Therapy (LLLT) in Reducing Postoperative Pain and Swelling After Third Molar Surgery - Meer, Ali Asmar; Haider, Muhammad Haseeb; Batool Kazmi, Syeda Allya Armaghana; Mehmood, Farah; Batool, Attia; Fatima, Syeda Samin; Khan, Laraib (Indus Journal of Bioscience Research, 2025)
Background: Third molar (wisdom tooth) extraction is a common oral surgical procedure often associated with postoperative complications such as pain, swelling, and trismus. Conventional treatments, including nonsteroidal anti-inflammatory drugs (NSAIDs) and corticosteroids, may be effective but are linked to systemic side effects. Low-Level Laser Therapy (LLLT) has emerged as a promising adjunctive treatment for minimizing postoperative discomfort due to its anti-inflammatory and biostimulatory properties. Objective: This meta-analysis aimed to evaluate the effectiveness of LLLT in reducing postoperative pain and swelling in patients undergoing third molar surgery. Methods: A systematic search was conducted in PubMed, Embase, Scopus, Web of Science, and Cochrane Library up to April 2024. Randomized controlled trials (RCTs) assessing LLLT versus placebo or standard care following third molar extraction were included. Primary outcomes were pain reduction measured by the Visual Analog Scale (VAS); secondary outcomes included facial swelling and trismus. The Cochrane RoB 2.0 tool was used for quality assessment. Pooled data were analyzed using a random-effects model, and standardized mean differences (SMDs) with 95% confidence intervals (Cis) were calculated using RevMan 5.4. Results: Three RCTs with a total of 130 participants were included. LLLT significantly reduced postoperative pain on days 1 and 3 compared to placebo (SMD = -1.05; 95% CI: -1.65 to -0.45; p = 0.001; I² = 52%). Similarly, swelling was significantly reduced on days 2 and 3 (SMD = -0.88; 95% CI: -1.32 to -0.45; p = 0.0001; I² = 40%). Sensitivity analysis confirmed the robustness of results, and no studies were assessed as having high risk of bias overall. Conclusion: LLLT appears to be a safe and effective adjunct in reducing pain and swelling after third molar surgery. Its non-invasive nature and favorable safety profile support its clinical utility. However, further large-scale, standardized RCTs are recommended to confirm these findings and optimize treatment parameters.